Leishmanicidal activity of green tea leaves and pomegranate peel extracts on L. infantum. Issue 24 (17th December 2019) - Imperatori, Francesca; Barlozzari, Giulia; Scardigli, Arianna; Romani, Annalisa; Macrì, Gladia; Polinori, Norma; Bernini, Roberta; Santi, Luca
Abstract: Leishmania infantum is responsible for the cutaneous and visceral form of this zoonotic disease, which is potentially lethal for humans and has dogs as natural reservoir. In the light of the antiparasitic properties displayed by several natural products, L. infantum promastigotes were exposed to green tea ( Camellia sinensis ) leaves extract (GTE) and pomegranate ( Punica granatum ) peel extract (PPE). Both extracts, characterized by NMR and HPLC analysis, inhibited parasite proliferation in a dose-dependent manner, as proved by IC50 evaluation determined by MTT assay.Moreover, the reversibility assay showed that GTE and PPE have an aptotosis-mediated leishmanicidal effect, as evidenced by DNA degradation and confirmed by DNA fragmentation and real-time PCR analyses. Finally, for the first time morphological and ultrastructural alterations induced by a P. granatum extract on Leishmania were shown by the use of light, transmission and scanning electron microscopy. Abstract :